The EU's new paediatric medicines legislation: serving children's needs?. Issue 9 (22nd August 2007) - Permanand, Govin; Mossialos, Elias; McKee, Martin
Abstract : In new legislation for paediatric medicines which came into effect on 26 January 2007, the European Union (EU) has attempted to address several unresolved issues relating to children's needs for medicines in Europe. This article reviews the legislation's main proposals and makes some comparisons with equivalent legislation in the USA. We argue that the legislation suffers from several gaps and uncertainties in relation to the specific proposals and their intended aims. As the establishment of new legislation in this area offered the EU an opportunity to set some clear guidelines and objectives, and had the potential to go beyond the equivalent American rules, we thus see the proposals as something of a disappointment.